Calcareous plankton and shallow-water benthic biocalcifiers: Resilience and extinction across the Cenomanian-Turonian Oceanic Anoxic Event 2 - Petrizzo, Maria Rose; Parente, Mariano; Falzoni, Francesca; Bottini, Cinzia; Frijia, Gianluca; Steuber, Thomas; Erba, Elisabetta (Palaeogeography, palaeoclimatology, palaeoecology, 2025)
Oceanic Anoxic Event 2 (OAE 2), spanning the Cenomanian/Turonian boundary (93.9 Ma), was an episode of major perturbation of the global carbon cycle. Its geochemical signature is a synchronous positive δ13C excursion in both carbonates and organic matter that resulted from the net burial of large amounts of organic carbon in deep-sea and hemipelagic settings. Causes for OAE 2 are still the subject of investigations; however, several studies postulate that massive submarine volcanic activity emitted greenhouse gases and provided biolimiting metals in marine ecosystems, leading to the onset of the Cenomanian-Turonian thermal maximum and to the enhancement of ocean fertility. Ocean temperature, sea-surface stratification, nutrient availability, and carbonate ion saturation were subject to variations during OAE 2 that resulted in fluctuations in diversity abundance and calcification of species. We analyzed the record of the main biocalcifiers of pelagic-hemipelagic settings (planktonic foraminifera and calcareous nannofossils) and of low-latitude carbonate platforms (larger benthic foraminifera and rudist bivalves) by looking at well-dated sections. Carbon isotope stratigraphy allowed precise correlation from shallow to deep water and tied the biotic response to the record of geochemical proxies of paleoenvironmental changes. The main extinction event, severely affecting the shallow-water benthic biocalcifiers and to a minor extent the calcareous plankton, occurred within and after the Plenus Cold Event. Fluctuations in surface seawater temperature and extreme warming were probably the main cause of extinction, with contributions from decreased seawater carbonate saturation and disruption of ocean stratification. Overall, calcareous plankton fared much better, showing a greater resilience than carbonate-platform biocalcifiers to paleoenvironmental perturbations across OAE 2. •Biotic events across the OAE 2 from carbonate platforms to deep basins.•Carbon isotope stratigraphy used for high-resolution platform to basin correlation.•Large benthic foraminifera and aragonite-dominated rudists suffered severe extinction.•Calcareous plankton and nannoplankton were much more resilient.•Extreme fluctuations of SST and warming probably the main cause of extinction.